Sub-Poissonian angular momentum distribution near threshold in atomic ionization by short-laser pulses - Arbo, Diego (2008)
We analyze the angular momentum distribution of electrons near threshold in atomic ionization by short laser pulses. The radial fanlike pattern in the two-dimensional momentum distribution observed in experiments is controlled by the dominance of a few angular momenta of the order l0. We find a semiclassical expression for l0 strongly dependent on the quiver amplitude of the detached electron but independent of the atomic species. The value of l0 can be also related to the minimum number of absorbed photons needed to reach the threshold. The strongly peaked sub-Poissonian angular distribution precludes a description by a stochastic random walk model in angular momentum.